Syariah-Compliant Legal Framework for Franchising: A Malaysian Legal Perspective - Hua Siong WONG (Communications of International Proceedings, 2020)
Since the enforcement of the Franchise Act 1998, Malaysia has been promoting the Franchise Industry extensively via the government bodies by providing financial assistance to the would be Franchisors and Franchisees. Some people in the Franchise Industry commented that the Act was said to be more pro Franchisee rather than pro Franchisor as some salient terms and conditions in the Act are stricter on the Franchisors. Others commented otherwise. This is where we will look in depth of the Act as Islam does not allow oppression in dealings. Nevertheless, with a few amendments recently made by the Domestic Trade, Co-operatives and Consumerism Ministry have in a way try to balance the interests of both parties concerned. This paper will look into whether the terms and conditions in the Franchise Act deviates from the Syariah principles and if yes, this paper will look into some proposals on how to make the Franchise Business and Industry Syariah friendly and thus making it competitive in the Islamic Finance Industry. The objective of this study is to ascertain the importance of amending the Franchise Act to be in Syariah compliance as in some circumstances the Franchisors and Franchisees are Muslims and to ensure no element of usury and gharar exist. Meanwhile, the author would like to evaluate the operation of the Franchise Industry in Malaysia as not to be in contradiction with Syariah principles. This will not only by looking at the Franchise Agreement but also the Franchisor’s Standard Operating Procedures and Operation Manuals. The research methodology requires gathering relevant data from both primary and secondary sources. Quran, Hadis, reports, statistics, specified journals and online articles help in order to analyze the material and arrive at a more complete understanding and historical reconstruction of the importance amending the Franchise Act and subsequently the Franchise Agreement to be Syariah compliance. This is qualitative study that involves a systematic study of philosophical and academic views though literatures. Therefore, this study is not an empirical study but rather a library study from various primary data sources such as Quran, Hadis, franchising agreement and secondary data sources namely articles and journals from online database. The study found that challenges faced by local entrepreneurs in franchise industry in Malaysia include the issues of prohibition against the same business, financial concern and monopoly by the franchisor. As such, it is suggested that the need for unique legal framework for Islamic franchising business in Malaysia in order to protect the local entrepreneurs, especially Muslim entrepreneurs in franchise industry.
Keywords: Franchising law; Syariah legal framework; Syariah compliant business; Malaysia.